Internalization of Character Education Values in Arabic Language Learning at Islamic Boarding School in Indonesia - Alwi, Said; Syukran, Syukran; Sari, Mutia (Institut Agama Islam Negeri Palangka Raya, 2024)
Arabic language teachers have significant roles and challenges in internalizing character values through Arabic language learning. Teachers are responsible for teaching vocabulary and grammar and must also be able to convey character education values. This research aims to determine the concrete form of internalizing character education values through the Arabic language learning process at Ulumuddin Islamic Boarding School in Lhokseumawe, Aceh. This study employs a descriptive qualitative research design. The data sources include observations during the Arabic language learning and interviews with teachers and students at Ulumuddin Islamic Boarding School in Lhokseumawe, Aceh. The data analysis follows Miles and Huberman's approach, involving data collection, reduction, display, and conclusion. The research findings indicate that the concrete form of internalizing character education values through Arabic language learning encompasses planning, implementation, and evaluation of the learning process. In practice, teachers use interactive, collaborative, and applicative teaching methods, enabling students to not only master the Arabic language but also develop positive character values. The internalization of character education values through Arabic language learning can contribute to shaping a generation that is not only intellectually smart but also possesses character values, following the requirements of the Aceh Regulation of 2022 to strengthen the implementation of Islamic character education.